Chimeric Antigen Receptor-Modified T Cells for Solid Tumors: Challenges and Prospects - Guo, Yelei (J Immunol Res, 2016)
Recent studies have highlighted the successes of chimeric antigen receptor-modified T- (CART-) cell-based therapy for B-cell malignancies, and early phase clinical trials have been launched in recent years. The few published clinical studies of CART cells in solid tumors have addressed safety and feasibility, but the clinical outcome data are limited. Although antitumor effects were confirmed in vitro and in animal models, CART-cell-based therapy still faces several challenges when directed towards solid tumors, and it has been difficult to achieve the desired outcomes in clinical practice. Many studies have struggled to improve the clinical responses to and benefits of CART-cell treatment of solid tumors. In this review, the status quo of CART cells and their clinical applications for solid tumors will be summarized first. Importantly, we will suggest improvements that could increase the therapeutic effectiveness of CART cells for solid tumors and their future clinical applications. These interventions will make treatment with CART cells an effective and routine therapy for solid tumors.